2021
DOI: 10.1177/20499361211048572
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RNA in the Cerebrospinal Fluid of a Patient with Long COVID

Abstract: Over 10% of COVID-19 convalescents report post-COVID-19 complications, namely, ‘long COVID’ or ‘post-COVID syndrome,’ including a number of neuro-psychiatric symptoms. The pathophysiology of COVID-19 in the central nervous system is poorly understood but may represent post-COVID injury, ongoing sterile maladaptive inflammation, or SARS-CoV-2 persistence. We describe a long COVID patient with SARS-CoV-2 RNA in the cerebrospinal fluid, which seems important, specifically due to recent reports of gray matter volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The presence of persistent viral reservoirs of SARS-CoV-2 has been proposed as a possible explanation of PASC pathophysiology [ 26 ]. Studies in macaques and humans demonstrated viral replication can persist months after initial infection in multiple organ systems [ 27 30 ] and viral presence in cerebrospinal fluid has been observed in neurological PASC [ 31 ]. Alternatively, damage resulting from severe disease during acute infection has also been proposed as a cause of PASC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of persistent viral reservoirs of SARS-CoV-2 has been proposed as a possible explanation of PASC pathophysiology [ 26 ]. Studies in macaques and humans demonstrated viral replication can persist months after initial infection in multiple organ systems [ 27 30 ] and viral presence in cerebrospinal fluid has been observed in neurological PASC [ 31 ]. Alternatively, damage resulting from severe disease during acute infection has also been proposed as a cause of PASC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of persistent viral reservoirs of SARS-CoV-2 has been proposed as a possible explanation of PASC pathophysiology (27). Studies in macaques and humans demonstrated viral replication can persist months after initial infection in multiple organ systems (28)(29)(30)(31) and viral presence in cerebrospinal fluid has been observed in neurological PASC (32). Alternatively, damage resulting from severe disease during acute infection has also been proposed as a cause of PASC (27).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple neurological symptoms such as loss of smell (anosmia), loss of coordination of movement (ataxia), headache, dizziness, increased vascular inflammation, encephalitis, and stroke have been observed following infection with SARS-CoV-2, which may indicate viral tropism for brain cells [52] . Recently, it has been reported that the SARS-CoV-2 genome was detected in the cerebrospinal fluid (CSF) and several reports suggest that respiratory viruses like SARS-Cov-2 may reach the CNS through various routes [53] , [54] . The olfactory pathway is one of the strongest candidate routes that contains several nerves [55] , [56] .…”
Section: Sars-cov-2 Infection and Cnsmentioning
confidence: 99%